Blockchain: : the chain for the changing marketing sphere - Amandeep Singh (2024)
Marketing has changed a lot in the past decade, but it is about to go through another revolution, thanks in large part to the blockchain. Yes, while most of us associate digital marketing with things like AI and analytics, blockchain may be the most disruptive technology yet to hit marketers in every industry. Blockchain is changing digital marketing, and you may be surprised who will benefit. Blockchain has brought a drastic change to the technology in the last few years and it is referred to as Distributed Ledger Technology (DLT), making the historical backdrop of any computerized resource unalterable and straightforward using decentralization and cryptographic hashing. A straightforward relationship for comprehension of blockchain innovation is a Google Doc. At the point when we make a record and offer it to a gathering of individuals, the archive is dispersed rather than replicated or moved. Indeed, the real impact of blockchain in digital marketing is not just in the new use cases being developed. It is in how those use cases will impact entire systems that have popped up to manage the digital marketplace. In a time when digital marketing seems to be changing and growing by the moment, blockchain is changing digital marketing in disruptive, perhaps even irreversible ways. This book will be useful to all who are involved in using Blockchain technology along with researchers and policymakers. No doubt, the intermediary of Blockchain technology and its marketers will also benefit from going through this book. The book will provide proper insights into Blockchain technology to students and creates a topical interest